Analisa Pengaruh Atmosfer Toko terhadap Perilaku Belanja Konsumen pada Gerai Farmers Market Area Jakarta Utara - Putri Hardiyanti (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
This research aimed to know the influence of store atmosphere on customer behavior at Farmers Market’s outlets in North Jakarta Area. Data collection method is done by spreading the questionnaire to measure consumer behavior response to store atmosphere variables. The number of samples taken in this study is 135 respondents who have been to Farmers Market’s outlet in Baywalk Mall and Mall Kelapa Gading in the last 6 months. Data analysis technique of the research was qualitative analysis and using a simple linear regression method. The R-Square for this research model indicates that all of store atmosphere factors has a simultanious correlations with customer behaviour. Partial test result (t-test) showed that store atmosphere variable (with ambience, space and function sub-variables, as well as signs, symbols, and artifacts sub-variables) had positive influences on customer behavior variable. A very interesting findings from this research indicates that store atmospheric factors have a positive correlation with customer behaviors.